A Study On Tourist Beha Vior Towards The Intention To Select Sustainable Tourist Destination - Koay, Tze Wei (2014)
The purpose of this study is to examine the tourist behavior towards the intention to select sustainable tourist destination. Tourism industry has been considered as one of the largest industries worldwide. With understanding of the tourist behavior, this could ensure the growth of the tourism industry in a more sustainable ways in respect of environment, social-cultural and economic factors. The understanding of the tourist behaviors in this study consist of the environmental attitudes, motivation, destination image, word-of-mouth and perceived service quality to predict the intentional behaviors of the selection of the sustainable tourist destination. In addition, knowledge has been included to explore the moderating relationship with the environmental attitudes. The theoretical framework is developed based on the theory of planned behavior. A total of 159 respondents were collected to CatTY out the SPSS and Smart PLS analysis. The statistical results showed that environmental attitudes, motivation and word-of-mouth significantly related to the intention to select sustainable tourist destination. However, the destination image and perceived service quality have no significant relationship in this study.